Large hydropower and legitimacy: A policy regime analysis, applied to Myanmar. (November 2017) - Foran, Tira; Kiik, Laur; Hatt, Sullivan; Fullbrook, David; Dawkins, Alice; Walker, Simon; Chen, Yun
Abstract: Hydropower development in capacity-constrained countries can unfold through unsound policy arguments, narrow institutional and implementing arrangements, and ad hoc decision making processes. To derive insights for more legitimate policy making, we provide the first holistic account of Myanmar's legitimation struggles over large hydropower, focusing on Myitsone, the country's most controversial dam, during the period 2003–2011. Our analysis takes a policy regime perspective (specifically, a "political economic regime of provisioning" framework). Among our findings: (1) frequent use of non-rationally persuasive argument among contending actors; (2) a spiral of declining policy legitimacy, which is amplified by civil society mobilization, and halted by a 2011 decision to suspend Myitsone; (3) rejection of Myitsone but conditional acceptance of large hydropower among some elements of civil society. Opportunity and capability for more technically informed, inclusive discussion exists in Myanmar, but given hydropower's complexities, urgently deserves to be augmented. Although Myitsone in Myanmar is an exceptional case, we offer three propositions to assess and improve policy legitimacy of hydropower. Highlights: First holistic analysis of hydropower policy legitimation struggles in Myanmar. Contention is necessary to re-legitimize a failing hydropower policy regime. A weakened or disrupted policy regime yields new opportunities for reform. We recommend inclusive stakeholder deliberation and multi-objective planning.